2016
DOI: 10.3847/0004-637x/830/1/29
|View full text |Cite
|
Sign up to set email alerts
|

TESTING THE BINARY TRIGGER HYPOTHESIS IN FUors

Abstract: We present observations of three FU Orionis objects (hereafter, FUors) with nonredundant aperturemask interferometry (NRM) at 1.59 µm and 2.12 µm that probe for binary companions on the scale of the protoplanetary disk that feeds their accretion outbursts. We do not identify any companions to V1515 Cyg or HBC 722, but we do resolve a close binary companion to V1057 Cyg that is at the diffraction limit (ρ = 58.3 ± 1.4 mas or 30 ± 5 AU) and currently much fainter than the outbursting star (∆K ′ = 3.34 ± 0.10 mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Binarity and outburst behavior has been examined in several studies (e.g., Bonnell & Bastien 1992;Reipurth et al 2002;Millan-Gabet et al 2006;Green et al 2016). As noted earlier, FU Ori is itself a 0 5 binary, and disk-binary interactions could promote an episodic or burst mode of accretion (Reipurth & Aspin 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binarity and outburst behavior has been examined in several studies (e.g., Bonnell & Bastien 1992;Reipurth et al 2002;Millan-Gabet et al 2006;Green et al 2016). As noted earlier, FU Ori is itself a 0 5 binary, and disk-binary interactions could promote an episodic or burst mode of accretion (Reipurth & Aspin 2004).…”
Section: Discussionmentioning
confidence: 99%
“…"Outside-in" models are those in which gravitationally bound fragments develop at large radii (tens of astronomical units or more) due to infall from a protostellar envelope, then migrate inward through the disk, ultimately generating an outburst when they accrete onto the star (e.g., Vorobyov & Basu 2015). A third option that has been posited is an external perturber-the interaction of the disk with an exterior massive object that alters the balance of accretion and triggers the cascading flow (Bonnell & Bastien 1992), although recent studies suggest the refill rate is too slow to occur on few coorbit timescales (Green et al 2016). The wavelength dependence of any postoutburst variability can distinguish among these classes of models.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in Sec 4.2, HBC 494 might also be a binary, pending confirmation from higher resolution observations. However, studies trying to connect disc outburst with multiplicity have so far been inconclusive (e.g., Millan-Gabet et al 2006;Green et al 2016) and there is no clear evidence that the multiplicity statistics from outbursting sources are any different from those of non-outbursting young stellar objects. Everything considered (low-disc mass and lack of clear connection with multiplicity), it seems likely that the EXor phenomenon is connected to instabilities of the inner disc (e.g., D Angelo & Spruit 2012) and/or planet-disc interactions (Clarke et al 1990, Lodato & Clarke 2004).…”
Section: Implications For Outburst Mechanismmentioning
confidence: 99%
“…Bonnell & Bastien (1992) initially suggested that FUor outbursts are induced by the tidal effect of the companion object in a binary system. At least some FUors are in binaries (e.g Koresko et al 1991;Green et al 2016…”
mentioning
confidence: 99%